Pembangunan Aplikasi Penjualan dan Pelayanan Pelanggan pada PT. Mega Abadi Motorindo - Putra Firman Ardiansyah; Denny Sagita Rusdianto; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
With the development of the economy marked by the era of globalization and the rapid advancement of technology, allows the availability of means for the fulfillment of customer needs will goods and services becomes much easier. That situation will make the intense competition between both companies of them produce products or services. Therefore, the sales and the customer service in a companies becomes the key to competing. To make it easier, the service to customers like to know info about promo, like a promo good bike or purchase reminder time service the motor it can be done via the social messaging service that I've integrated the system with WhatsApp. The results of the research there were six actors, eighty-one functional needs. As well as the test results are 100% valid.